2005
DOI: 10.1128/jb.187.7.2483-2490.2005
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Terminal Oxygenase Component of Cumene Dioxygenase fromPseudomonas fluorescensIP01

Abstract: The crystal structure of the terminal component of the cumene dioxygenase multicomponent enzyme system of Pseudomonas fluorescens IP01 (CumDO) was determined at a resolution of 2.2 Å by means of molecular replacement by using the crystal structure of the terminal oxygenase component of naphthalene dioxygenase from Pseudomonas sp. strain NCIB 9816-4 (NphDO). The ligation of the two catalytic centers of CumDO (i.e., the nonheme iron and Rieske [2Fe-2S] centers) and the bridging between them in neighboring cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
79
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 39 publications
5
79
0
2
Order By: Relevance
“…However, this remains to be substantiated via cloning of NdmA and NdmB individually. Some Rieske oxygenases are known to be in hexameric a 3 b 3 configuration (Dong et al, 2005;Friemann et al, 2005;Kauppi et al, 1998;Yu et al, 2007) but only the a subunits contain the [2Fe-2S] cluster and the mononuclear ferrous iron, while the b subunits are mainly for structural purposes (Ferraro et al, 2005). The 2-oxo-1,2-dihydroquinoline 8-monooxygenase of P. putida 86 was reported to be in an a 6 configuration, determined by gel filtration chromatography (Rosche et al, 1995), but the crystal structure showed that it is actually a homotrimer (Martins et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, this remains to be substantiated via cloning of NdmA and NdmB individually. Some Rieske oxygenases are known to be in hexameric a 3 b 3 configuration (Dong et al, 2005;Friemann et al, 2005;Kauppi et al, 1998;Yu et al, 2007) but only the a subunits contain the [2Fe-2S] cluster and the mononuclear ferrous iron, while the b subunits are mainly for structural purposes (Ferraro et al, 2005). The 2-oxo-1,2-dihydroquinoline 8-monooxygenase of P. putida 86 was reported to be in an a 6 configuration, determined by gel filtration chromatography (Rosche et al, 1995), but the crystal structure showed that it is actually a homotrimer (Martins et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several three-dimensional (3D) structures of ROs are currently available (3,4,6,7,8,9,13,15,17,19,20), including a single 3D structure of KshA, namely, that of M. tuberculosis H37Rv (Rv3526; KshA H37Rv ) (2). Although the protein sequences of ROs vary considerably, their tertiary structures are very similar overall.…”
mentioning
confidence: 99%
“…Characteristic for ROs, including KshA H37Rv , is the formation of trimers. These trimers either occur as ␣3 subunits (2,4,17,19) or may additionally include a smaller ␤ subunit of the oxygenase component, resulting in an (␣␤)3 enzyme complex (3,6,7,8,9,13,15,20). The active site of KshA H37Rv was shown to be composed of a ␤ sheet, including a loop region located at the entrance of the active site, flanked by two ␣ helices.…”
mentioning
confidence: 99%
“…The 3D structure was determined by molecular replacement, using the α-subunit from naphthalene dioxygenase from Pseudomonas sp. Strain NCIB 9816-4, [6] and the β-subunit from cumene dioxygenase from P. fluorescens strain IP01, CDO-O IP01 [11] as templates. The model was refined using REFMAC [12] and COOT [13] to R and R free factors of 19.7 and 23.6 %, respectively (Fig.…”
mentioning
confidence: 99%